A high-resolution (0.1° × 0.1°) inventory of methane emissions from Canadian and Mexican oil and gas systems. (June 2017) - Sheng, Jian-Xiong; Jacob, Daniel J.; Maasakkers, Joannes D.; Sulprizio, Melissa P.; Zavala-Araiza, Daniel; Hamburg, Steven P.
Abstract: Canada and Mexico have large but uncertain methane emissions from the oil/gas industry. Inverse analyses of atmospheric methane observations can improve emission estimates but require accurate source patterns as prior information. In order to serve this need, we develop a 0.1° × 0.1° gridded inventory of oil/gas emissions in Canada for 2013 and Mexico for 2010 by disaggregating national emission inventories using best available data for production, processing, transmission, and distribution. Results show large differences with the EDGAR v4.2 gridded global inventory used in past inverse analyses. Canadian emissions are concentrated in Alberta (gas production and processing) and Mexican emissions are concentrated along the east coast (oil production). Highlights: A 0.1° × 0.1° inventory of oil/gas methane emissions is done for Canada and Mexico. The inventory provides an improved prior estimate for inversion of methane. Canadian emissions are concentrated in Alberta (gas production and processing). Mexican emissions are concentrated along the east coast (oil production).